Transforaminal endoscopic discectomy: a targeted spinal surgery - Mor Japar Khan, Ed Simor Khan; Kow, Ren Yi (2019)
Introduction Open discectomy has been the gold standard of care for cases of prolapsed intervertebral disc. Tissue dissection is unavoidable in order to access the pathologic disc material. After skin incision, subcutaneous fat tissue, paraspinal muscles, ligamentum flavum, epidural fat, dura and nerve roots has to be encountered before reaching the disc material. With the in out transforaminal endoscopic technique, only skin and subcutaneous tissue need to be bridged before reaching the disc material. Also known as the targeted surgical technique, this technique minimized the trauma to the soft tissue. Materials and methods We present 3 case series of prolapsed intervertebral disc which was treated with transforaminal endoscopic technique. Case 1 49 year old lady presented with one year history of low back pain and left lower limb sciatica. Straight leg raising sign was positive. MRI showed 2 level disc bulge at L4L5, L5S1 with annular tear at L5S1. At 2 weeks post op pain was improved by 60% and SLR test was negative. case 2 26 year old lady presented with 6 months history of low back pain and left lower limb sciatica. Straight leg raising sign was positive. MRI showed extruded disc at L4L5. At post op day one, her sciatica completely resolved and SLR test was negative. Case 3 28 year old lady presented with 8 months history of low back pain and left lower limb sciatica. Straight leg raising sign was positive. MRI showed extruded disc at L5S1 with annular tear. At post op day one, her sciatica completely resolved and SLR test was negative. Results All three patients underwent transforaminal discectomy. Case 1 and 2 were done under monitored anaesthesia control (MAC) and case 3 was done under epidural anaesthesia. All three patients had satisfactory pain relief. The 1st patient had longer recovery period possibly because of its disease chronicity. Conclusion Early recovery is expected hence early return to work can be accomplished. In the future this might be the gold standard of treating prolapsed intervertebral disc.